Spices as natural additives for beef burger production - Sedlacek-Bassani, Juliana [UNESP]; Grassi, Thiago Luís Magnani [UNESP]; Diniz, Juliana Campos Pereira [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (FapUNIFESP (SciELO), 2020)
This study aimed to investigate if the inclusion of different spices in bovine burger affects bacterial growth, lipid oxidation and sensorial characteristics of the products. Four hamburger formulations were prepared: control (without additives), saffron (1%), ginger (1%) and urucum (1%). The products were analyzed for total bacterial count (TBC) on days 0, 7 and 15 (storage at 4 °C) and 0, 15 and 60 (storage at -30 °C) and, for rancidity, on days 0, 30 and 60 (storage at -30 °C). The acceptance of the sensory attributes and the purchase intent were evaluated using hedonic scales. All burgers formulated with spices and kept at 4 °C had lower TBC than the control formulation, whereas for those stored at -30 °C, the same occurred only with the ginger-made ones. Lower lipid oxidation was found for the formulations containing the spices. Control and ginger formulations led the acceptance of the tasters for the attributes appearance and color, besides that, aroused greater interest in the purchase intention trial. It was concluded that the addition of spices reduced TBC and delayed the lipid oxidation of hamburgers, and that the products elaborated with ginger had the highest sensory acceptance and purchase intention indexes.
Keywords: Bacterial load; Bixa orellana; Chemical oxidation; Consumer behavior; Curcuma; Ginger